Reconstruction With 3D-Printed Prostheses After Sacroiliac Joint Tumor Resection: A Retrospective Case-Control Study - Pu, Feifei; Liu, Jianxiang; Shi, Deyao; Huang, Xin; Zhang, Jingtao; Wang, Baichuan; Wu, Qiang; Zhang, Zhicai; Shao, Zengwu (Frontiers in Oncology, 2022)
Background: Sacroiliac joint tumor is rare and the reconstruction after tumor resection is difficult. We aimed to analyze and compare the clinical effects of three-dimensional (3D) printed prostheses and bone cement combined with screws for bone defect reconstruction after sacroiliac joint tumor resection. Methods: Twelve patients with sacroiliac joint tumors who underwent tumor resection and received 3D-printed prostheses to reconstruct bone defects in our hospital from January 2014 to December 2020 were included in the study group Twelve matched patients who underwent sacroiliac joint tumor resection and reconstruction with bone cement and screws in the same time period were selected as the control group. Results: In the 3D-printing group, six cases were extensively excised, and six cases were marginally excised. All patients were followed up for 6–90 months, and the median follow-up time was 21 months. Among them, nine patients had disease-free survival, two survived with tumor recurrence, and one died due to tumor metastasis. The MSTS-93 score of the surviving patients was 24.1±2.8. The operation time was 120.30±14.50 min, and the intraoperative bleeding was 625.50±30.00 mL. In the control group, seven cases were extensively excised, and five cases were marginally excised. All patients were followed up for 6–90 months, with a median follow-up time of 20 months. Among them, nine patients had disease-free survival, one survived with tumor recurrence, and two died due to tumor metastasis. The MSTS-93 score of the patients was 18.9±2.6. The operation time was 165.25±15.00 min, and the intraoperative bleeding was 635.45±32.00 mL. There was no significant difference in survival status, intraoperative blood loss, or complications between the two groups (P>0.05). However, there were statistically significant differences in operative time and postoperative MSTS-93 scores between the two groups (P<0.05). Conclusions: After resection of the sacroiliac joint tumor, reconstruction using 3D printed prostheses was shorter and resulted in better movement function.